The exoteric/esoteric divide and Schellenberg's Sceptical Religion. Issue 1 (16th November 2017) - DUMSDAY, TRAVIS
Abstract: In a ground-breaking series of books, Canadian philosopher J. L. Schellenberg (2005d; 2007b; 2009; 2013a) has developed a systematic non-theistic, non-naturalist philosophy of religion. One of the core claims within his system is that given our limited evidence (and limited capabilities for assessing what evidence we do have), scepticism concerning the truth of religious propositions is at present the only warranted epistemic response. In this article I draw attention to a potential complication for Schellenberg's assessment of the pragmatic implications of this evidential situation, a complication arising from the distinction between exoteric and esoteric religion.